Interplay between integrins and cadherins to control bone differentiation upon BMP-2 stimulation - Anne Valat; Laure Fourel; Adria Sales; Paul Machillot; Paul Machillot; Anne-Pascale Bouin; Carole Fournier; Lauriane Bosc; Mélanie Arboléas; Ingrid Bourrin-Reynard; Amy J. Wagoner Johnson; Amy J. Wagoner Johnson; et al. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Upon BMP-2 stimulation, the osteoblastic lineage commitment in C2C12 myoblasts is associated with a microenvironmental change that occurs over several days. How does BMP-2 operate a switch in adhesive machinery to adapt to the new microenvironment and to drive bone cell fate is not well understood. Here, we addressed this question for BMP-2 delivered either in solution or physically bound of a biomimetic film, to mimic its presentation to cells via the extracellular matrix (ECM).Methods: Biommetics films were prepared using a recently developed automated method that enable high content studies of cellular processes. Comparative gene expressions were done using RNA sequencing from the encyclopedia of the regulatory elements (ENCODE). Gene expressions of transcription factors, beta chain (1, 3, 5) integrins and cadherins (M, N, and Cad11) were studied using quantitative PCR. ECM proteins and adhesion receptor expressions were also quantified by Western blots and dot blots. Their spatial organization in and around cells was studied using immuno-stainings. The individual effect of each receptor on osteogenic transcription factors and alkaline phosphatase expression were studied using silencing RNA of each integrin and cadherin receptor. The organization of fibronectin was studied using immuno-staining and quantitative microscopic analysis.Results: Our findings highlight a switch of integrin and cadherin expression during muscle to bone transdifferentiation upon BMP-2 stimulation. This switch occurs no matter the presentation mode, for BMP-2 presented in solution or via the biomimetic film. While C2C12 muscle cells express M-cadherin and Laminin-specific integrins, the BMP-2-induced transdifferentiation into bone cells is associated with an increase in the expression of cadherin-11 and collagen-specific integrins. Biomimetic films presenting matrix-bound BMP-2 enable the revelation of specific roles of the adhesive receptors depending on the transcription factor.Discussion: While β3 integrin and cadherin-11 work in concert to control early pSMAD1,5,9 signaling, β1 integrin and Cadherin-11 control RunX2, ALP activity and fibronectin organization around the cells. In contrast, while β1 integrin is also important for osterix transcriptional activity, Cadherin-11 and β5 integrin act as negative osterix regulators. In addition, β5 integrin negatively regulates RunX2. Our results show that biomimetic films can be used to delinate the specific events associated with BMP-2-mediated muscle to bone transdifferentiation. Our study reveals how integrins and cadherins work together, while exerting distinct functions to drive osteogenic programming. Different sets of integrins and cadherins have complementary mechanical roles during the time window of this transdifferentiation.